2006
DOI: 10.1016/j.virol.2006.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of HIV-1 Vif-Cul5 E3 ubiquitin ligase through a novel zinc-binding domain-stabilized hydrophobic interface in Vif

Abstract: APOBEC3G (A3G) and related cytidine deaminases are potent inhibitors of retroviruses. HIV-1 Vif hijacks the cellular Cul5-E3 ubiquitin ligase to degrade APOBEC3 proteins and render them ineffective against these viruses. Here, we report that HIV-1 Vif is a novel zinc-binding protein containing an H-x(5)-C-x(17-18)-C-x(3-5)-H motif that is distinct from other recognized classes of zinc fingers. Zinc-binding stabilized a conserved hydrophobic interface within the HCCH motif that is critical for Vif-Cul5 E3 assem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
125
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(138 citation statements)
references
References 61 publications
12
125
1
Order By: Relevance
“…Our finding that Vif interacts with zinc is consistent with two recent studies (14,15) in which zinc and Vif were found to interact. We were concerned, however, that the observed zinc binding by full-length Vif could be due to one or more of the 17 His residues not contained in the HCCH motif (in addition to the 6x His tag, HIV-1 HXB2 Vif contains 11 His residues outside the HCCH motif).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding that Vif interacts with zinc is consistent with two recent studies (14,15) in which zinc and Vif were found to interact. We were concerned, however, that the observed zinc binding by full-length Vif could be due to one or more of the 17 His residues not contained in the HCCH motif (in addition to the 6x His tag, HIV-1 HXB2 Vif contains 11 His residues outside the HCCH motif).…”
Section: Resultssupporting
confidence: 93%
“…Several reports (9,10,12,(14)(15)(16)(17)(18)(19) have shown that mutations in the recently defined HCCH motif impair Vif function. In one report (19), Vif C114 (amino acid numbering used hereafter refers to the HIV-1 HXB2 Vif sequence) was proposed to constitute part of a cysteine protease active site involved in gp41 processing.…”
mentioning
confidence: 99%
“…Whether a substrate receptor recruits Cul2 or Cul5 depends on an additional Cullin binding interface. In the case of cellular substrate receptors, Cullin selection is determined by the presence of a VHL or SOCS box motif (11), in the case of HIV and SIV, a zinc-stabilized helix mediates Cul5 selection (12)(13)(14)(15)). …”
mentioning
confidence: 99%
“…The BC box motif creates a hydrophobic interface for binding to EloC. The Cullin box has a specific site for binding to Cul5, which involves an interaction between the highly conserved HCCH zinc-binding motif in Vif and the N-terminal domain (NTD) of Cul5 (22,23).…”
mentioning
confidence: 99%